2021
DOI: 10.1186/s13102-021-00328-7
|View full text |Cite
|
Sign up to set email alerts
|

Physical and psychological health outcomes of a sitting light volleyball intervention program on adults with physical disabilities: a non-randomized controlled pre-post study

Abstract: Background People with physical disabilities (PWPD) have limited opportunities to participate in sport activities. Sitting light volleyball (SLVB) is an adapted sport that combines light volleyball and paralympic sitting volleyball. This study examined the effectiveness of an SLVB intervention program to improve the physical and psychological health outcomes of PWPD in Hong Kong, China. Methods Thirty-two PWPD [13 women; SLVB group, n = 18; control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…Measuring the quality of life of Paralympic athletes, we found that PWDs who play sports evaluate their QOL favorably as found in the literature (Freire et al, 2019a;Wellichan;Leung et al, 2021;Calheiros et al, 2021;Szeliga et al, 2022;Mira et al, 2022).…”
Section: Discussionsupporting
confidence: 67%

Qualidade de Vida de Pessoas com Deficiência Motora, Praticantes ou não de Paradesporto

Karollyni Bastos Andrade Dantas,
Gabriel Gastélum-Cuadras,
David Arnoldo García Fernández
et al. 2024
Retos
“…Measuring the quality of life of Paralympic athletes, we found that PWDs who play sports evaluate their QOL favorably as found in the literature (Freire et al, 2019a;Wellichan;Leung et al, 2021;Calheiros et al, 2021;Szeliga et al, 2022;Mira et al, 2022).…”
Section: Discussionsupporting
confidence: 67%

Qualidade de Vida de Pessoas com Deficiência Motora, Praticantes ou não de Paradesporto

Karollyni Bastos Andrade Dantas,
Gabriel Gastélum-Cuadras,
David Arnoldo García Fernández
et al. 2024
Retos
“…According to a previous study that applied domestic various exercise programs, ball exercise for strengthening the trunk muscle strength of disabled person with spastic cerebral palsy showed a signi cant effect in lying and ipping, four-legged crawling, and knee standing in the gross motor function. Participating in in sport activities has physical and psychological bene ts for adults with physical disabilities (12) but, According to a previous study that applied public various exercise programs, Active children have better postural control than sedentary children, Children who are active in physical activity practice have better posture control. The sedentary lifestyle should be reduced in the child population.…”
Section: Introductionmentioning
confidence: 99%